Lectin-Like Binding of Four Animal Lactobacilli Considered for their Use in Probiotical Preparations - I. Štyriak ,; I. Štyriaková, (Journal of Pharmacy and Nutrition Sciences, 2016)
Four gut lactobacilli (Lactobacillus plantarum L5, Lactobacillus paracasei L81, Lactobacillus fermentum L 670 and Lactobacillus casei subsp. pseudoplantarum L.c.) were examined by particle agglutination assay (PAA) for their lectin-like binding activity after their cultivation on Rogosa agar and in MRS broth. Seven ECM (extracellular matrix) molecules (bovine mucin, porcine mucin, bovine fibronectin, porcine fibronectin, fetuin, bovine lactoferrin and heparin) were selected for this assay. Moreover, haemagglutination tests with pig, cattle, sheep, and hen erythrocytes were performed. However, none of the four Lactobacillus strains examined did react with any of the erythrocytes tested. The differences between individual strains were observed in their binding to immobilised ECM molecules. The best adherent were the Lactobacillus plantarum L5 and Lactobacillus paracasei L81, however, the other two strains showed also good ECM binding of some ECM proteins. With regard to an influence of cultivation medium on lectin-like binding activity, binding of all ECM molecules was expressed in Lactobacillus paracasei L81 to significantly higher degree after cultivation on Rogosa agar than in MRS broth. Similarly, strains Lactobacillus fermentum L670 and Lactobacillus casei subsp. pseudoplantarum L.c. displayed significantly higher binding of fibronectin and mucin after growth on Rogosa agar in comparison with MRS broth cultivation. The influence of cultivation medium on fetuin binding by Lactobacillus fermentum L670 was also not significant while Lactobacillus casei subsp. pseudoplantarumL.c. bound fetuin significantly better after growth on Rogosa agar. Heparin pretreatment increased the binding of the ECM molecules by the Lactobacillus fermentum L 670 strain significantly with the exception of porcine fibronectin when the strain was cultivated in MRS broth. Similar positive effect of heparin was observed also in the other three lactobacilli. This result is important especially in the connection with the observations that heparin decreased ECM binding of enteropathogens as staphylococci or clinical enterococcal isolates. Following up on some earlier strain characteristics, these results confirm that the selected lactobacilli are suitable for probiotic purposes.